Knowledge and use of Cactaceae in rural communities in the semi-arid region of Paraíba, northeastern Brazil - Pedrosa, Kamila Marques; Lima-Nascimento, Ailza Maria de; Carvalho, Thamires Kelly Nunes; Lucena, Camilla Marques de; Lopes, Sérgio de Faria; Lucena, Reinaldo Farias Paiva de (Ethnobotany Research and Applications, 2020)
Background: Cactaceae species are physiologically adapted to regions with arid and semi-arid climates, in which they are available and often used by traditional communities. This study aimed to analyze how ethnobotanical knowledge is influenced by socioeconomic factors such as age and gender in a semi-arid region of Paraíba, Brazil. Methods: This study was conducted in rural communities in the semi-arid region of Paraíba, northeastern Brazil. The data were collected by applying a semi-structured questionnaire to 44 informants (30 men and 14 women). The average age of the informants was 39 years; however, women were 39–77 and men were 31–80 years old. The chi-square test was used to analyze differences regarding knowledge, according to gender and age. The influence of gender (male and female) and age in the distribution of uses per category and species was assessed through the Poisson distribution model. Results: The following native species were recorded: Cereus jamacaru DC. subsp. jamacaru, Melocactus zehntneri, Pilosocereus gounellei (F.A.C. Weber) Byles & G.D. Rowley subsp. gounellei, Pilosocereus pachycladus F.Ritter, Tacinga inamoena (K. Schum.) N.P. Taylor & Stuppy, and Tacinga palmadora (Britton & Rose) N.P. Taylor & Stuppy, which had 436 citations in different categories of use (food, fuel, construction, fodder, medicinal, technology, and others). Our results indicated that residents cite more uses for fodder, food, and medicinal purposes. C. jamacaru had the highest UV and young men cited more uses for the species. Conclusions: Social variables tend to influence residents’ knowledge. Among the categories of use, the residents indicated a higher number of uses for fodder and C. jamacaru was the most prominent species. Keywords: Ethnobotany; Caatinga; Socioeconomic Factors; Use Value